FACTORS ASSOCIATED WITH PHYSICAL, PSYCHOLOGICAL AND SOCIAL FRAILTY AMONG MIDDLE-AGED AND OLDER HOMELESS WOMEN - Salem, B (Innov Aging, 2018)
The purpose of this exploratory analysis was to assess factors associated with physical, psychological and social frailty among middle-aged and older homeless (N=120) enrolled from a community site servicing homeless women. Guided by the Frailty Framework among Vulnerable Populations (FFVP), a principal component analysis (PCA) was used to construct frailty factor indices for situational factors (i.e., incarcerated, chronically homeless, trauma history), behavioral factors (i.e., drug dependency, alcohol use, emergency room use), mental health-related factors (i.e., depressive, anxiety and PTSD symptoms), physical health-related factors (i.e., falls, pain, comorbidities), and resource factors (i.e., social support, coping, spirituality). Simple linear regressions were used to assess unadjusted relationships and multiple linear regressions assessed adjusted associations with physical, psychological and social frailty. PCA average loadings included situational (M=.439, range: .44-.57), behavioral (M=.560, range: .36-.67), mental health-related (M=.577, range: .57-.59), physical health-related (M=.577, range: .57-.58) and resource (M=.427, range: .21-.55) factors. Controlling for FFVP model factors, people with > 12 years of education and/or college/certificate had less psychological frailty (β=-.49, p=.016). Behavioral factors were significantly associated with physical frailty (β=.52, p=.002). Mental health-related factors were significantly associated with physical frailty (β=.65, p<.001), social frailty (β=.17, p=.007) and overall frailty (β=.98, p<.001). Physical health-related factors were significantly associated with psychological frailty (β=.35, p<.001) and overall frailty (β=.97, p<.001). Resource factors had a non–significant association between physical frailty (β=-.21, p=.089) and overall frailty (β=-.27, p=.054). FFVP model factors and physical, psychological and social frailty relationships exist which will guide intervention development for middle-aged and older homeless women.